Rancang Bangun Aplikasi Manpower Request Bagian Recruitment pada PT Dynapack Asia - Listiani Listiani; Friska Natalia (ULTIMA InfoSys, 2019)
PT Dynapack Indonesia is a packaging and plastics company and part of Dynapack Asia. PT Dynapack Indonesia consists of several divisions, one of them is IT division which has Application Development sub division that is in charge of designing and developing application which is needed for the company. PT Dynapack Indonesia is a multinational company, that it is necessary to maintain the quality of human resources, considering the Human Resources (HR) division is a strategic factor for both profit organizations and non-profit organizations (Yuniarsih & Sugiharto, 2016). Therefore, the IT division of PT Dynapack Indonesia developed a web-based Manpower Request application system with the purpose of assisting HR division in recruiting process to data archiving. Development of Manpower Request application system uses CodeIgniter framework, jQuery, Metronic, Bootstrap, SAP and MySQL database. Testing, fixing bugs, and updates has done while the application is being developed. Manpower Request application is ready to use and has been made in accordance with requirements. Keywords: CodeIgniter, human resources, recruitment, website